To send or not to send … that is the question. Issue 11 (23rd February 2018) - Zacarese, Lawrence M.
Abstract : Recently, our emergency management colleagues in Hawaii faced every emergency manager's worst nightmare: sending a "live" alert to countless recipients in error. To make matters worse, this was not an alert warning about a traffic condition or the cancellation of a music concert or a rip current advisory. No, this was the worst possible scenario that I and many other practitioners could imagine. This was an alert to the entire state indicating that a ballistic missile was incoming and advising them to seek shelter immediately. Adding insult to the initial injury, there was a 38‐minute delay before an official message was delivered indicating that the first was sent in error and that there wasn't actually a missile threat. What happened next was not surprising. Fingers pointed, knees jerked, blame was placed, and calls were made for immediate reforms regarding the way the Hawaii Emergency Management Agency handles its alerts. My advice? Be careful what you wish for.